(untitled) (Applied Biological Research, 2024)
Iron is an essential micronutrient for all living organisms because of its critical role in metabolic processes. In plants it plays a key role in the synthesis of chlorophyll, some vital enzymatic and metabolic processese. However, most of the iron in nature is present as precipitates or in insoluble forms. Therefore, biological mechanism has been employed to mineralize Fe(III) oxides into Fe(II) through microbial action to increase the availability of soluble iron. An iron reducing bacterial strain was isolated based on its tolerant limits and iron mineralizing ability. The strain Bacillus sp. SP10 effectively mineralized iron in synthetic medium possessing 1% starch and pH 7. In a 25 day’s column study, the soluble Fe(II) as micronutrient showed a gradual increase in each seepage collected from different treatment columns. Similarly, the plants grown on soil obtained from treatment D (i.e. 1% starch + 1% Bacillus sp. SP10 inoculum + 0.25% anthraquinone-2,6-disulphonate) column displayed good growth and maximum shoot length, mainly due to the increased accessibility of iron through microbial mineralization. The mineralization of Fe in soil was established through SEM and EDX analysis.